2016
DOI: 10.1002/mus.24993
|View full text |Cite
|
Sign up to set email alerts
|

Median and ulnar nerve anastomoses in the upper limb: A meta‐analysis

Abstract: As anastomoses between the median and ulnar nerves occur commonly, detailed anatomical knowledge is essential for accurate interpretation of electrophysiological findings and reducing the risk of iatrogenic injuries during surgical procedures. Muscle Nerve 54: 36-47, 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
86
0
9

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 78 publications
(100 citation statements)
references
References 53 publications
(382 reference statements)
5
86
0
9
Order By: Relevance
“…Other common variations included anastomoses between the ulnar and median nerves at the level of the digital nerves to fingers four and five, which was observed in 57% of specimens. These findings are similar to findings in the previous literature on an anastomosis in the same area named the Berretini anastomosis which has a prevalence of 60.9% [13]. We would like to acknowledge that other variations in the anatomy of the UN are possible; however, they were not seen in the samples studied.…”
Section: Discussionsupporting
confidence: 90%
“…Other common variations included anastomoses between the ulnar and median nerves at the level of the digital nerves to fingers four and five, which was observed in 57% of specimens. These findings are similar to findings in the previous literature on an anastomosis in the same area named the Berretini anastomosis which has a prevalence of 60.9% [13]. We would like to acknowledge that other variations in the anatomy of the UN are possible; however, they were not seen in the samples studied.…”
Section: Discussionsupporting
confidence: 90%
“…Items for the AQUA Tool were generated on the basis of (1) the extensive background of the steering committee in conceiving and executing anatomical metaanalyses and systematic reviews, and (2) a review of the anatomical literature (Andall et al, 2015;Henry et al, 2015aHenry et al, , 2015bRamakrishnan et al, 2015;Roy et al, 2015;Tomaszewski et al, 2016aTomaszewski et al, , 2016bTomaszewski et al, , 2016cTomaszewski et al, , 2016dVikse et al, 2016). No comprehensive systematic review of systematic reviews was performed because there was no previously-used quality assessment of anatomical studies, and the number of true evidence-based reviews and meta-analyses in the literature is limited.…”
Section: Preliminary Conceptual Design and Item Generationmentioning
confidence: 99%
“…), and the extensive background of the steering committee in conducting meta-analyses and systematic reviews of anatomical studies (Andall et al, 2015;Henry et al, 2015aHenry et al, , 2015bRamakrishnan et al, 2015;Roy et al, 2015aRoy et al, , 2015bTomaszewski et al, 2016aTomaszewski et al, , 2016bTomaszewski et al, , 2016cTomaszewski et al, , 2016dVikse et al, 2016), we developed a preliminary conceptual design for the AQUA Checklist. In addition to items considered standard in reporting all medical studies (sample size, demographics, results, etc.…”
Section: Preliminary Conceptual Design and Item Generationmentioning
confidence: 99%
“…In that context, the authors of the present study have developed the Anatomical Quality Assurance (AQUA) Checklist, the aim of which is to improve the quality of reporting of anatomical studies. From our extensive experience of evidence-based anatomical studies (Andall et al, 2015;Henry et al, 2015aHenry et al, , 2015bRamakrishnan et al, 2015;Roy et al, 2015aRoy et al, , 2015bTomaszewski et al, 2016aTomaszewski et al, , 2016bTomaszewski et al, , 2016cTomaszewski et al, , 2016dVikse et al, 2016), we have found that such studies are often poorly reported, thus decreasing their reliability and increasing the risk of bias. A high reporting quality is imperative since understanding and knowledge of anatomy allows for successful clinical interventions.…”
Section: Introductionmentioning
confidence: 99%